An Analysis of The City Meaning in Three Paintings by Agung Tato (Semiotics Approach Of Charles Sanders Peirce’) - Indra Tjahyadi (Sekolah Tinggi Kesenian Wilwatikta Surabaya, 2021)
A painting is not just a meaningless manifestation of human artisticcreation. A painting is also a manifestation of a meaningful signcreated by a painter. This article focuses its study on the meaning ofthe city that is represented in three paintings by Agung Tato entitledSecond Level, City of Tommorow, and B…..The theory that it is usedto reveal the meaning of the three paintings by Agung Tato is CharlesSanders Peirce's semiotics theory. The method which used in thisstudy is an interpretive qualitative method. The interpretation factorof the sign which the basis of the analysis work is the factor that leadsthe choice of this method in this article. Based on the analysis that hasbeen done, it was found that in Agung Tato's painting of the city isinterpreted as an inhumane geography. Human is no longer as asubject who becomes central to the development or growth of a city.The city exists as a city itself, apart from the various living things inthe universe.